Where splicing joins chromatin - Hnilicová, Jarmila; Staněk, David (Nucleus (Austin, Tex.), 2011)
There are numerous data suggesting that two key steps in gene expression-transcription and splicing influence each other closely. For a long time it was known that chromatin modifications regulate transcription, but only recently it was shown that chromatin and histone modifications play a significant role in pre-mRNA splicing. Here we summarize interactions between splicing machinery and chromatin and discuss their potential functional significance. We focus mainly on histone acetylation and methylation and potential mechanisms of their role in splicing. It seems that whereas histone acetylation acts mainly by alterating the transcription rate, histone methylation can also influence splicing directly by recruiting various splicing components.
Keywords: sestřih RNA; RNA Splicing; Nucleoproteins; Transcription, Genetic; nucleosome; prekurzory RNA; chromatin; nukleoproteiny; genetická transkripce; Chromatin; alternative splicing; RNA Precursors; Animals; lidé; Transcription Factors; transkripční faktory; Humans; zvířata; histone methylation; snRNP; transcription; exon; histone acetylation